Investigation of Anticipatory Postural Adjustments during One-Leg Stance Using Inertial Sensors: Evidence from Subjects with Parkinsonism - Bonora, Gianluca; Mancini, Martina; Carpinella, Ilaria; Chiari, Lorenzo; Ferrarin, Maurizio; Nutt, John G.; Horak, Fay B. (Frontiers in Neurology, 2017)
The One-Leg Stance test (OLS) is a widely adopted tool for the clinical assessment of balance in the elderly and in subjects with neurological disorders. It was previously showed that the ability to control anticipatory postural adjustments (APAs) prior to lifting one leg is significantly impaired by idiopathic Parkinson’s disease (iPD). However, it is not known how APAs are affected by other types of parkinsonism, such as frontal gait disorders (FGD). In this study, an instrumented OLS test based on wearable inertial sensors is proposed to investigate both the initial anticipatory phase and the subsequent unipedal balance. The sensitivity and the validity of the test have been evaluated. Twenty-five subjects with iPD presenting freezing of gait (FOG), 33 with iPD without FOG, 13 with FGD and 32 healthy elderly controls were recruited. All subjects wore three inertial sensors positioned on the posterior trunk (L4-L5), and on the left and right frontal face of the tibias. Participants were asked to lift a foot and stand on a single leg as long as possible with eyes open, as proposed by the mini-BESTest. Temporal parameters and trunk acceleration were extracted from sensors and compared among groups. The results showed that, regarding the anticipatory phase, the peak of medio-lateral trunk acceleration was significantly reduced compared to healthy controls (p<0.05) in subjects with iPD with and without FOG, but not in FGD group (p=0.151). Regarding the balance phase duration, a significant shortening was found in the three parkinsonian groups compared to controls (p<0.001). Moreover, balance was significantly longer (p<0.001) in iPD subjects without FOG compared to subjects with FGD and iPD subjects presenting FOG. Strong correlations between balance duration extracted by sensors and clinical mini-BESTest scores were found (ρ>0.74), demonstrating the method’s validity. Our findings support the validity of the proposed method for assessing the OLS test and its sensitivity in distinguishing among the tested groups. The instrumented test discriminated between healthy controls and people with parkinsonism and among the three groups with parkinsonism. The objective characterization of the initial anticipatory phase represents an interesting improvement compared to most clinical OLS tests.